Peningkatan Pengetahuan pada Ibu Hamil tentang Kelas Ibu sebagai Upaya Pencapaian Program Kelas Ibu Hamil - Intan Monik Pratami (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
The health of pregnant women is very important, health must be done as much as possible, if the mother is not healthy, the child will also follow what the mother is facing. There are many bad effects if the health of pregnant women is not right, one of which can make the death of pregnant women. This is a common problem in society. The purpose of the class for pregnant women is to increase knowledge, change attitudes and behavior of mothers to understand pregnancy, body changes and complaints during pregnancy, pregnancy care, childbirth, postpartum care, postnatal family planning, infectious diseases and birth certificates (MOH 2011, p. 2). The method used to increase the knowledge of pregnant women is counseling education. The author hopes that after this counseling education is carried out, pregnant women can find out the importance of maternal chelation during pregnancy. The results that can be obtained are increasing knowledge of pregnant women about the importance of participating in Mother's class activities in Jatibarang Kidul Village, the output obtained is the existence of health education media about Mother's Class in Jatibarang Kidul Village.